Ngamp ngangk minangam ilyamp thant pam wanch. antan a! = 1 Corinthians 13. - Wycliffe Bible Translators (Darwin : Wycliffe Bible Translators, 1980)
Translation of 1 Corinthians 13 into Wik-Mungkan.
Keywords: Education - Language - Indigenous languages; Religions - Christianity - Bible translations; Wik Mungkan language (Y57, Y143) (Qld SD54-07); Aurukun map area (Qld NW Cape York SD54-07)